Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents - Plank, Anne-Christine; Maschke, Janina; Rohleder, Nicolas; Fasching, Peter A.; Beckmann, Matthias W.; Kornhuber, Johannes; Eichler, Anna; Moll, Gunther H.; Kratz, Oliver (Frontiers in Immunology, 2021)
Background/Aim: Determining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of biobehavioral studies, the potential of DBS CRP and sCRP to discriminate between defined BMI subgroups was assessed. Materials and Methods: CRP levels in DBS and saliva collected from 87 healthy adolescents (M = 13.25 years, SD = 0.30, 51.7% females) were determined using high sensitive CRP ELISA for serum and salivary CRP ELISA, respectively. Characteristics and correlation of both measurements were assessed for the total sample and for three subgroups classified by BMI percentile ranges (A: ≤ 25; B: 26-74; C: ≥ 75). Results: In the total sample, DBS CRP and sCRP were significantly associated (r = 0.59, p < 0.001). Splitting the sample into BMI-dependent subgroups revealed similarly strong associations of DBS CRP with sCRP for all three groups (A: r = 0.51; B: r = 0.61; C: r = 0.53). However, comparing the mean CRP values per BMI subgroup, one-way ANOVA reported significant differences for DBS CRP, but not for sCRP mean values. Conclusions: The significant correlation of DBS CRP with sCRP was independent of the investigated BMI range groups, yet BMI-dependent distinction was only provided by DBS CRP mean values. Overall, our results suggest that DBS CRP is likely to reflect systemic inflammation more precisely. Salivary CRP can be alternatively determined in studies with adolescents when conditions require it, given the oral health status is assessed. Considering that DBS CRP and sCRP share only 35% of common variance, further studies should examine their specific validity.